Pengaruh Literasi Keuangan yang Dimoderasi Tata Kelola Keuangan terhadap Kinerja Keuangan UMKM Rumah Makan di Kecamatan Cisaat Kabupaten Sukabumi - Fitriani Fitriani; Iqbal Noor; Acep Suherman (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the effect of financial literacy, consisting of financial knowledge, financial attitude, and financial awareness, on the financial performance of restaurant MSMEs in Cisaat District, Sukabumi Regency, with financial governance as a moderating variable. This research applied a quantitative approach using a survey method. Data were collected through questionnaires distributed to 80 owners or managers of restaurant MSMEs. The sampling technique used was purposive sampling, and the data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results show that financial knowledge, financial attitude, and financial awareness do not significantly affect MSME financial performance. In contrast, financial governance has a positive and significant effect on financial performance. The moderation test indicates that financial governance does not moderate the relationship between financial knowledge, financial attitude, financial awareness, and financial performance. These findings suggest that the improvement of restaurant MSME financial performance is more strongly determined by practical, structured, and consistent financial governance than by financial literacy components alone.